1998
DOI: 10.1086/517365
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Colonization‐Associated Properties ofHelicobacter pyloriIsolated from Children and Adolescents

Abstract: Helicobacter pylori isolates from 32 children and adolescents were characterized with respect to putative virulence and colonization-associated properties. Only 3 of the subjects had duodenal ulcer. All but 2 of the remaining 29 had various degrees of chronic gastric inflammation. No significant correlation between degree of inflammation and presence of the cag-pathogenicity island, cytotoxin production, vacA alleles associated with cytotoxin expression, and binding ability to the Lewis(b) (Le[b]) oligosacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
1
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 12 publications
2
29
1
2
Order By: Relevance
“…Consistent with this observation, there is variation among H. pylori isolates in the capacity to bind to Lewis b (7,16,23,28 …”
mentioning
confidence: 52%
See 2 more Smart Citations
“…Consistent with this observation, there is variation among H. pylori isolates in the capacity to bind to Lewis b (7,16,23,28 …”
mentioning
confidence: 52%
“…Consistent with this observation, there is variation among H. pylori isolates in the capacity to bind to Lewis b (7,16,23,28). One study reported that 63 (66%) of 95 H. pylori isolates bound to Lewis b (16).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The finding that colonization with iceA2 strains is age correlated, being more common in older patients, has never been reported before. It could be related to age-dependent expression of host factors such as observed by Ç elik et al (8) for Le b receptors. iceA2 was more frequently found in males.…”
Section: Discussionmentioning
confidence: 77%
“…These authors demonstrated that bacterial adhesin to the Leb antigen is coded by the babA2 gene and is associated with the presence of the cagA gene. An interesting and surprising finding, demonstrated by Çelik et al [32] , is that children probably have few Leb receptors on surface mucous cells, which may explain the fact that susceptibility to colonization with a CagA-positive strain is linked to age.…”
Section: Discussionmentioning
confidence: 99%